Formação do indivíduo, formação docente e educação especial: o lugar do sujeito e o compromisso com a adaptação - Simões, Maria Cristina Dancham (2016)
This research dealt with the teacher training in a higher level, for the final years of secondary and high school levels in Brazilian basic education. It was sought the contributions from the Critical Theory of Society on formation and education, in the content of academic disciplines, educational plans and curriculum guides of the considered courses. This study aimed to examine aspects of teacher training, using as a background the education of people with disabilities, whose specific objectives were to collate the educational projects with the national curriculum guides for identifying and detailing possible tendencies; and to examine terminological differences referred to the theme of education of people with disabilities. The study sought to demonstrate the impossibility of affirming that future teachers are prepared to deal with the students and their singularities, whether disabled or not; that there is space, in the way the contents are configured, for the promotion of human dignity; that there are strategies or principles which define, as a horizon, the education of educators to break the reproduction and permanence of barbarism, violence, prejudice and social domination. About the terminological differences, it was possible to say that the disciplines offered are more related to disability itself than to people with disabilities. A tendency was found that leads to the shortening of the proposed studies and the emptying of the meanings of concepts and terms; and a fetishist posture towards an efficient performance, possibly aligned to the impositions to adaptation of the Cultural Industry, indicating it might have other purposes than the promotion of the living subject and a dignified human life, nevertheless is constantly proclaimed their defense. Yet the contradiction is precisely at the gap opened by the possibility of taking seriously what is just announced, although distorted and misrepresented, in the documents that regulate their operation